Psychometric properties of the Malay translated and adapted multicultural experience inventory-revised in the Malaysian context - Harun, Maizatul Mardiana; Wan Jaafar, Wan Marzuki; Ismail, Asmah; Mohd Noah, Sidek (UiTM Press, Universiti Teknologi MARA, 2022)
Personal multicultural experience may contribute to an individual’s competency in working with multicultural clients. Individuals with higher multicultural exposure and interactions are expected to have greater cultural resources that are crucial when working with diversity. Thus, this study aims to examine the psychometric properties of the Malaysian version of the Multicultural Experience Inventory-Revised (MEI-R). The MEI-R is a self-rated questionnaire that measures individuals’ multicultural exposure and interactions during their formative years and current multicultural encounters. This study involved 205 counsellor trainees who were selected using cluster random sampling. Previously the Malay translated and adapted MEI-R had undergone the preliminary exploratory factor analysis. In this study, the focus is to examine and confirm the factor structure, reliability and validity of the translated and adapted MEI-R. This study also reported the value of external validity. In this study, the results confirm the factor structure, reliability, and validity of the translated and adapted MEI-R. All in all, the translated and adapted MEI-R has high reliability and sufficient validity values, indicating that it may be used successfully on counsellor trainees of all genders.